2005
DOI: 10.1001/archsurg.140.7.625
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Endarterectomy in Nonagenarians

Abstract: Hypothesis:The North American Symptomatic Carotid Endarterectomy Trial and the European Carotid Surgery Trial demonstrated that a greater benefit from carotid endarterectomy (CEA) was seen in elderly compared with younger patients. However, no patients older than 89 years were included in either study. We hypothesized that CEA is safe and effective in patients 89 years and older.Design and Setting: This is a retrospective review of 3 neurosurgeons' CEA experience with nonagenarian patients.Participants and Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…These results reported by Durward et al 4 are certainly commendable and support my own bias that carotid endarterectomy should not be withheld, when otherwise indicated, simply on the basis of age alone. In our own experience with 182 carotid endarterectomies performed among 167 octogenarians (mean age, 83 years; range, 80-93 years), my colleagues and I found that the early postoperative results were as good for properly selected octogenarians as they were for younger patients.…”
Section: Commentarysupporting
confidence: 59%
See 1 more Smart Citation
“…These results reported by Durward et al 4 are certainly commendable and support my own bias that carotid endarterectomy should not be withheld, when otherwise indicated, simply on the basis of age alone. In our own experience with 182 carotid endarterectomies performed among 167 octogenarians (mean age, 83 years; range, 80-93 years), my colleagues and I found that the early postoperative results were as good for properly selected octogenarians as they were for younger patients.…”
Section: Commentarysupporting
confidence: 59%
“…3 Durward et al present a series of 26 patients, with a mean age of 91 years, who underwent 30 carotid endarterectomies for severe carotid stenosis. 4 The authors specify that all the patients were leading independent lives at the time of surgical consideration. The patients were accumulated over a 10-year period, and most procedures were done for focal or nonfocal neurologic symptoms, although 7 procedures were done for asymptomatic stenoses, 6 of which (86%) were progressive.…”
Section: Commentarymentioning
confidence: 99%
“…Only a few studies reported rates for nonagenarians. In-hospital mortality was 3.1% among 64 patients in one study [35], and 30-day mortality rates ranged from 0 to 6.3% [34,36] in studies of 26 and 16 patients, respectively. Many of these reports combined multiple years of data and did not describe changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data have been published on the long-term outcomes following CEA in nonagenarians. One study of 26 patients aged ≥90 years found a 15% 2-year mortality rate [36]. Data from the US National Vital Statistics Report show that the average 80-year-old in the USA has a 5-year survival of 70%, and the average 90-year-old has a 5-year survival of 42% with life expectancies of 9 and 5 years, respectively [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation